Diversity of Macroalgae in Sire Beach, North Lombok - Arianti, Alya; Pazila, Baiq Dinda Aluh Putri; Ramdhiani, Arsyka; Kurniawan, Ali; Kholidah, Baiq Maylina; Royani, Baiq Nurlatifa; Pratiwi, Baiq Dwi Sekarjati; Candri, Dining Aidil; Ghazali, Mursal (Jurnal Biologi Tropis, 2024)
Macroalgae are multicellular lower plant organisms that live in water, especially in marine waters. Macroalgae better known as marine algae are macroscopic algae that can reach several meters in length. Macroalgae are a highly diverse group of organisms in terms of morphology, level of structural complexity, and size. They play an important role in maintaining ocean water quality, reducing coastal erosion, and providing habitat for a wide variety of marine life. This study aimed to identify the macroalgae species present in the Sire Beach area and determine the ecological index of macroalgae in the Sire Beach area. This study was conducted from October to December 2024. Data collection was carried out using the transect method along the coastline with a transect size of 50 m perpendicular to the coastline. The macroalgae data found in this study are categorized into three classes, seven orders, seven families, nine genera, and 15 species of macroalgae. The macroalgae types found include eight species of the phylum Chlorophyta, four species of the phylum Phaeophyta, and three species of the phylum Rhodophyta. Chlorophyta (green algae) is the most common type of macroalgae in Shira Beach. The diversity index (H\') in this study was 2.47, indicating a moderate diversity of macroalgae. The evenness index value obtained is 0.91 which indicates that the evenness value is high. The dominance index in this study is 0.11 which indicates that the level of dominance is low. The obtained Margarev's wealth indicator is 3.69, indicating that the richness of the seeds is moderate.